Metaphorical Phraseologies in a Learner Corpus: Investigating Translations from Brazilian Portuguese to English (Revista de Estudos da Linguagem, 2024)
This paper discusses the results of a study that aimed to examine whether Brazilian learners face difficulties in translating metaphorical phraseologies into English from a lexical, semantic, and cognitive perspective. The study drew on four main fields of research: metaphor, translation, phraseology, and corpus linguistics. We applied the conceptual metaphor theory and the cognitive-discourse perspective to identify the conceptual and linguistic metaphors in the corpus under study. Based on the cognitive translation hypothesis, mapping conditions were examined in the source and target languages. Additionally, grounded on corpus linguistics and phraseology, we evaluated the conventionality of the translated phraseologies in terms of their lexicogrammar, semantic, metaphor, and contextual features using a co-occurrence method and concordance line analysis. The research findings, along with related empirical studies, are presented and discussed. A total of 21 learners translated 81 phraseologies, resulting in 1202 translation solutions. The analysis showed that 86% of the translations represented metaphors with similar mapping conditions. However, 42% of them were understood as less or non-conventional metaphorical phraseologies. The findings suggest that the linguistic aspect posed more of a challenge in the translations rather than the conceptual one. Learners retained the conceptual metaphor in the target language, but they often used unusual lexical choices in English due to the influence of their mother tongue’s cognitive-linguistic system.